CHILD’S READINESS FOR SCHOOL AS PRIORITY SUBJECT DETERMINANT - Pantiuk, Tetiana; Nevmerzhytska, Olena; Ivakh, Svitlana; Perkhun, Lesia; Yarushak, Maria (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The article deals with the issue of a child’s readiness for school as an important personal determinant and a holistic system of child’s individual characteristics. The child’s readiness for school has been considered in the research holistically. It involves the development of motivational and cognitive activity, the level of formation of communication mechanisms, analytic-synthetic and volitional activities. Complex characteristics of physiological, mental, motivational and intellectual components of the preschooler’s readiness for school have been taken into account. The objective of the article consists in analyzing the child’s readiness for organized schooling as an important subjective determinant and justification of the cause-and-effect relationship between preschooler readiness for school and family education. Certain criteria for the six-year-old children’s psychophysiological readiness for school in the process of conducting a comprehensive study have been considered. They are as follows: the health group (first or second); the level of physical and motor development in relation to age and sex norms; sensorimotor properties and skills; intellectual development, social maturity. In order to diagnose the child’s readiness for school the following methods have been used in the research: an experimental conversation to identify a preschooler’s internal position (by T. Nezhnova); school readiness assessment (by Kern’s-Yerasek test); the technique of “Graphic Dictation” (by D. Elkonin); the test “Preservation of Quantity” (by J. Piaget); Philippine test etc. Based on the study of parents' involvement in the process of preparing children for school, the conditionality of the child's level of readiness is substantiated by the system of factors, certain conditions of the family in which she was brought up.The study proves that the child’s successful transition from pre-school to school is possible on condition that the child has developed appropriate physical, social and mental skills ensuring his/her readiness for school. The integrity of the process of the child’s preparation for school and the development of the above mentioned components are the key to the child’s further progress and socialization at school.